Progress towards universal health coverage and inequalities in infant mortality - Hone, Thomas (2024)
Funding Information: This research was funded by the UK National Institute for Health and Care Research (grant numbers NIHR133252 and NIHR150067) using UK aid from the UK Government to support global health research. The views expressed in this publication are those of the authors and not necessarily those of the National Institute for Health and Care Research or the UK Department of Health and Social Care. Publisher Copyright: © 2024 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY 4.0 license